Pengaruh Paparan Informasi Politik di Media Sosial Terhadap Sikap Politik Generasi Muda - Hasan, Ahmad Daffa; Minan, Jeni; Subekti, Sugeng Agus (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
The development of social media has brought about significant changes in the way communication occurs, including in conveying public issues among the younger generation who are active users of digital platforms. Currently, social media is not only used as a means of entertainment and interaction, but also as a primary source of information related to public issues and policies. This study aims to determine the extent to which exposure to information on social media can influence the attitudes of the younger generation towards public issues. The approach used was quantitative with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method, which was processed using the SmartPLS application. Data were collected by distributing questionnaires with a five-point Likert scale to 100 young respondents who actively use social media and are frequently exposed to related information. The results of testing the measurement model indicate that all indicators have met the criteria for convergent validity and reliability. This is evident from the Average Variance Extracted (AVE) value which is above 0.50, as well as the Cronbach’s Alpha and Composite Reliability values ??which have exceeded the minimum limit of 0.70. Furthermore, the structural model found that exposure to information on social media has a positive and significant influence on the attitudes of the younger generation. This is indicated by the path coefficient value of 0.655 with a significance level of p < 0.05. The R-square value of 0.429 indicates that the information exposure variable is able to explain 42.9% of the variation in attitudes of the younger generation, while the remainder is influenced by other factors outside the model. These findings demonstrate that social media has a significant role in shaping the perspectives of the younger generation, especially through the intensity of exposure and how the information is packaged. Therefore, this study is expected to contribute to the development of digital communication studies, as well as serve as a consideration in efforts to improve the literacy of the younger generation to be more critical in responding to information circulating on social media.